The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5380/ce.v27i0.83499
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização Dos Atendimentos De Urgência Clínica Em Uma Maternidade De Risco Habitual: Estudo Transversal

Abstract: Objetivo: caracterizar os atendimentos do pronto atendimento de uma maternidade de risco habitual. Método: pesquisa quantitativa, transversal e retrospectiva, com análise dos indicadores de um pronto atendimento de uma maternidade de uma capital do sul do Brasil, de janeiro de 2018 a dezembro de 2019. Dados analisados de forma descritiva. Resultados: dos 25.451 atendimentos, 24.307 eram gestantes, 944 puérperas, 119 mulheres que sofreram aborto, 46 não gestantes e 35 indefinidos. A média de atendimentos mens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Travel distance may hold ambiguous and divergent meanings in retrospective studies, mainly when analyzed in the context Patients could be discouraged from seeking their local health service if they are frequently referred to nearby cities, just to be discharged hours later without needing further intervention, spending significant time on what could potentially be solved at the primary care level. This hypothesis is partially corroborated by research in Brazil, which observed high rates of nonurgent or low-priority cases among pregnant patients of all gestational ages in obstetric emergency departments (23,24) or high discharge rates from the specialized obstetric emergency department after clinical assessment and verbal orientation (25).…”
Section: Discussionmentioning
confidence: 74%
“…Travel distance may hold ambiguous and divergent meanings in retrospective studies, mainly when analyzed in the context Patients could be discouraged from seeking their local health service if they are frequently referred to nearby cities, just to be discharged hours later without needing further intervention, spending significant time on what could potentially be solved at the primary care level. This hypothesis is partially corroborated by research in Brazil, which observed high rates of nonurgent or low-priority cases among pregnant patients of all gestational ages in obstetric emergency departments (23,24) or high discharge rates from the specialized obstetric emergency department after clinical assessment and verbal orientation (25).…”
Section: Discussionmentioning
confidence: 74%
“…É perceptível a importância do registro correto de todas as informações coletadas durante o atendimento da usuária, inexistência da ficha de classificação (Trigueiro et al, 2022).…”
Section: Falha Na Aplicação Do Instrumento De Aandcr E No Registro Do...unclassified
“…Percebe-se também como é fundamental a capacitação profissional da equipe de enfermagem para a execução e preenchimento correto e completo do A&CR. (Costa et al, 2019;Trigueiro et al, 2022).…”
Section: Falha Na Aplicação Do Instrumento De Aandcr E No Registro Do...unclassified